2021
DOI: 10.1055/a-1678-6556
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-Coding RNA Small Nucleolar RNA Host Gene 5 (SNHG5) Regulates Renal Tubular Damage in Diabetic Nephropathy via Targeting MiR-26a-5p

Abstract: The study explored the diagnostic value of SNHG5 in diabetic nephropathy (DN) and investigated the role and mechanism on DN via establishing the in vitro HK2 cell model. This study recruited 62 types 2 diabetes mellitus (T2DM) patients, 58 DN patients and 60 healthy controls (HC). The expressions of serum SNHG5 and miR-26a-5p were measured by RT-qPCR analysis. The diagnostic value of SNHG5 in DN was assessed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…In addition to the 103 review articles, a total of 246 studies were removed for the following reasons: 120 were animal studies, 108 did not report AUC values, and 18 did not report numerical sensitivity or specificity results. In total, 24 studies ultimately met our eligibility criteria, of which T2DM, DN, and DR were analyzed in 17, 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 5, 5 , 30 , 35 , 36 , 37 and 7 studies, 4 , 28 , 29 , 32 , 37 , 38 , 39 respectively (some articles included more than one of these outcomes). Table 1 provides the specifics of the survey characteristics and summarizes the quality assessment results.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the 103 review articles, a total of 246 studies were removed for the following reasons: 120 were animal studies, 108 did not report AUC values, and 18 did not report numerical sensitivity or specificity results. In total, 24 studies ultimately met our eligibility criteria, of which T2DM, DN, and DR were analyzed in 17, 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 5, 5 , 30 , 35 , 36 , 37 and 7 studies, 4 , 28 , 29 , 32 , 37 , 38 , 39 respectively (some articles included more than one of these outcomes). Table 1 provides the specifics of the survey characteristics and summarizes the quality assessment results.…”
Section: Resultsmentioning
confidence: 99%
“…Further, Cat et al. demonstrated that inhibition of Long Non-Coding RNA Small Nucleolar RNA Host Gene 5 (SNHG5) might mitigate HG-induced renal tubular damage via targeting miR-26a-5p [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, compelling evidence indicated that upregulated SNHG5 plays a vital role in neoplastic kidney disease ( 34 , 35 ). Regarding nonneoplastic kidney disease, a recent study indicated that SNHG5 expression was elevated in HK-2 cells treated with HG, accompanied with decreased cell viability, increased apoptosis, and enhanced inflammatory cytokines and oxidative stress ( 36 ). Nevertheless, the potential effects of SNHG5 in podocytes remain to be explored.…”
Section: Discussionmentioning
confidence: 99%